Sandwich immunoassay for adrenomedullin precursor and its practical application - Paul Kaufmann; Yulia Ilina; Michaela Press; Andreas Bergmann (Scientific Reports)
Abstract Adrenomedullin (ADM) is a multifaceted peptide hormone involved in numerous physiological processes, including vascular stability, vasodilation, angiogenesis, and anti-inflammatory responses. The processing of ADM results in several fragments, including midregional proadrenomedullin (MR-proADM), and glycine-extended ADM (ADM-Gly) and bioactive ADM (bio-ADM). MR-proADM, the stable ADM fragment, and bio-ADM, the active form of ADM with a short half-life, have been shown to be potent biomarkers in a variety of pathologies. ADM-Gly, the direct precursor of bio-ADM, is a predominant form in human plasma, but remains less understood and least investigated. This study presents the development of a specific immunoluminometric assay for the quantification of ADM-Gly and offers a robust one-step approach for large-scale sample screening. Applied to human and rodent plasma, it elucidates the release kinetics and plasma half-life of ADM-Gly. Our findings confirm the predominance of ADM-Gly in healthy individuals and its significant release under pathological conditions. Our immunoluminometric assay enables precise measurement of ADM-Gly, advancing research into ADM-related pathophysiology and supporting its use as a biomarker and therapeutic target in various diseases.